Protestantism: A State Religion during the Malagasy Monarchy - Rafenomanantsoa Emilson; Robijaona Rahelivololoniaina Baholy (Polit Journal Scientific Journal of Politics, 2026)
Emerging from the sixteenth-century European Reformation, Protestantism expanded dynamically, leading to the nineteenth-century insertion of the British Presbyterian movement into Madagascar. This article examines the institutionalization of Protestantism and the systemic transformations catalyzed by the strategic convergence between British missionaries and Malagasy sovereigns. Employing a qualitative, historical-critical methodology, this study analyzes an extensive corpus of administrative treaties, ecclesiastic archives, and historical documents to elucidate how this religious movement functioned as a primary mechanism of state modernization and political centralization. The empirical findings reveal that the London Missionary Society (LMS) systematically introduced scriptural literacy and a Western-style educational apparatus in Imerina from 1820 onward, utilizing pedagogical networks to accelerate evangelical conversion. Despite a three-decade period of aggressive state-enforced suppression under Queen Ranavalona I, the Protestant apparatus demonstrated profound structural resilience. Following the diplomatic liberalization of 1862, this socio-religious movement culminated in its historic elevation to the rank of de facto state religion under Queen Ranavalona II in 1869. The state-church alliance generated sweeping civilizational advancements, including the formation of native administrative cadres, the implementation of robust biomedical and hospital infrastructures, and significant innovations in material architecture. Simultaneously, this study highlights the dialectical tensions produced by social polarization, alongside the eventual emergence of a stable socio-cultural synthesis, exemplified by the integration of traditional ancestral customs within Christian liturgical practices. This undisputed Protestant hegemony permanently altered the island's institutional trajectory until 1896, when French colonial rule under Governor-General Gallieni systematically dismantled its structural privileges to favor Roman Catholicism.